CONSTRUCTION Process Analysis of Giant and Complex Steel Structures. Issue 2 (March 2020) - Chen, Junjie; Luan, Wei; Gong, Ke; Ma, Jun
Abstract: The main structure of Xi 'an Silk Road International Conference Centre is a giant steel braced frame structure. The façade of the structure is made up of huge suspended skirtlike suspended structure supported by cantilever roof trusses and steel suspensions, which adds up its complexity. In order to accurately control the installation precision and facilitate the installation of curtain wall glass in the later stage, the pre-chamber construction method is adopted in the roof truss installation to compensate the construction deformation of suspended structure. The static analysis is conducted by SAP2000 to propose a reasonable pre-camber value of the roof cantilever truss. The nonlinear simulation of the construction process is carried out. Through comparative analysis, the optimal sequence of the steel structure construction is obtained, which provides the theoretical basis for the construction of giant and complex steel structures.